2019
DOI: 10.1177/1535370219894302
|View full text |Cite
|
Sign up to set email alerts
|

αKlotho attenuates cardiac hypertrophy and increases myocardial fibroblast growth factor 21 expression in uremic rats

Abstract: In chronic kidney disease (CKD), evidence suggests that soluble αKlotho (sKlotho) has cardioprotective effects. Contrariwise, high circulating levels of fibroblast growth factor 23 (FGF23) are related to uremic cardiomyopathy development. Recently, it has been demonstrated that sKlotho can act as a soluble FGF23 co-receptor, allowing sKlotho to modulate FGF23 actions in the myocardium, leading to the activation of cardioprotective pathways. Fibroblast growth factor 21 (FGF21) is a cardiomyokine with sKlotho-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
(98 reference statements)
1
9
0
Order By: Relevance
“…The mechanisms of MR in CKD are poorly understood and may include hemodynamic and non-hemodynamic factors [ 26 , 27 , 28 , 29 , 30 , 31 ]. The increased production of fibroblast growth factor-23 [ 32 , 33 ], αKlotho [ 34 , 35 ], and calcitriol [ 36 ] deficiencies are major candidate non-hemodynamic factors of cardiomyopathy progression in patients with CKD [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of MR in CKD are poorly understood and may include hemodynamic and non-hemodynamic factors [ 26 , 27 , 28 , 29 , 30 , 31 ]. The increased production of fibroblast growth factor-23 [ 32 , 33 ], αKlotho [ 34 , 35 ], and calcitriol [ 36 ] deficiencies are major candidate non-hemodynamic factors of cardiomyopathy progression in patients with CKD [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies have demonstrated that sKL treatment prevents heart alterations found following renal dysfunction. Thus, sKL treatment was found to prevent FGF-23-induced cardiac hypertrophy ( Han et al, 2020 ; Suassuna et al, 2020 ) and dysfunction ( Navarro-García et al, 2020 ) in experimental CKD models. In this line, Klotho overexpression has been shown to prevent cardiac alterations in a uremic milieu ( Navarro-García et al, 2020 ).…”
Section: Fibroblast Growth Factor-23-klotho Axis As Therapeutic Target In Renal Diseasementioning
confidence: 97%
“…However, clinical studies on the therapeutic benefit of anti-FGFR4 antibodies in LVH are still pending. Treatment of uremic cardiomyopathy in rodents with recombinant αKlotho ameliorated LVH and fibrosis independent of high FGF23 synthesis ( Figure 3 ), but again, clinical studies are lacking to prove the positive effects of Klotho therapy on the CV system ( 121 ).…”
Section: Therapeutic Approaches To Reduce Fgf23's CV Comorbiditiesmentioning
confidence: 99%